Manajemen Pengembangan Musyawarah Guru Mata Pelajaran (MGMP) Sebagai Upaya Meningkatkan Kompetensi Profesional Guru PAI - Husna Amalia (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
Teacher professionalism is an important component that can determine success in the teaching and learning process in the classroom. In an effort to improve teacher professional competence there are several programs that can be done, one of them is by empowering Musyawarah Guru Mata Pelajaran (MGMP) for PAI teachers. MGMP is an opportunity for teachers to be able to develop themselves and innovate in developing the quality of learning in the classroom. This research is a literature review that aims to understand MGMP management as an effort to improve the professional competence of PAI teachers. The results of this study are MGMP requires planning, organizing, mobilizing and monitoring so that the objectives of the MGMP programs can contribute positively to the development of professional competencies for PAI teachers.